Trends in Mortality from Ischemic Heart Disease in the Region of the Americas, 2000-2019 - Fernando Lanas; Alvaro Soto (Ubiquity Press, 2022)
Background: In latest decades, mortality rates from ischemic heart disease (IHD) had declined steadily in most of the world as a consequence of improvements in prevention and therapy. Objective: The aim of this study was to analyze trends in mortality caused by IHD in the region of the Americas from 2000 to 2019. Methods: Estimates of the age-adjusted mortality rate (AAMR) due to IHD were extracted from the Data Portal on Noncommunicable Diseases, Mental Health, and External Causes (ENLACE), Pan American Health Organization. We used Joinpoint regression to analyze significant changes in mortality trends by country, gender, geographical sub-region, and country income, according to the World Bank classification. We also calculated the average annual percent change (AAPC) mortality rate for the overall period in the Americas as a whole and by country and sub-region. Results: In the region of the Americas, the AAMR from IHD decreased from 117.80 (95% uncertainty interval (UI)) 106.64-135.90) in 2000 to 73.64 (62.65-92.66) per 100,000 in 2019. In males, from 149.08 (95% UI 138.23-168.08) to 96.02 (95% UI 83.48-117.19) and in females 92.36 (95% UI 81.35-109.42) to 54.84 (95% UI 45.28-71.76). The AAPC mortality rate in the region decreased -2.5% (95% CI: -2.7, -2.3), with joinpoints in 2007 and 2012, -2.3% (95% CI: -2.5, -2.1) in men and -2.7% (95% CI: -3.0, -2.5) in women. According to the sub-region analysis, the highest decrease was recorded in North America, AAPC -3.1% (95% CI: -3.3, -3.0) with one joinpoint in 2011, whereas there was a stagnation of the mortality rate in Central America, Mexico, and Latin Caribbean with an AAPC of 0.1 (-0.2, 0.3) with one joinpoint in 2007. Conclusions: Age-adjusted mortality rate from IHD between 2000 and 2019 has decreased in the region of the Americas. However, different trends were observed, North America had the highest reduction in AAPC, while Central America, Mexico, and Latin Caribbean Region had a stagnation. This trend was highly influenced by country income.